Effects of Nutraceuticals and Botanicals on Macrophage Cholesterol Efflux: Implications for Atherosclerosis - Sotherden, Grace Megumi; Uto-Kondo, Harumi; Ayaori, Makoto; Ikewaki, Katsunori (Journal of Nutritional Therapeutics, 2013)
To date, the literature on high-density lipoprotein (HDL) levels as an inverse risk factor for atherosclerosis has mainly been observational, and it is likely that the metabolism and function of HDL is a more significant determinant of cardiovascular disease. As an example, as cholesterol is effluxed out of macrophages and carried to the liver via HDL for excretion, reduced cholesterol efflux can result in increased cholesterol accumulation. In terms of atherosclerosis risk, increasing cholesterol efflux is theoretically a strategy that can be considered as the groundwork of cardiovascular disease treatment and prevention. However, until now, there has not been a pharmaceutical agent that has effectively increased reverse cholesterol transport (RCT) at all steps of the process. Here is a review of the research on natural compounds present in edible foods and their observed in vitro and in vivo (and even ex vivo) effects on the first step of RCT: macrophage cholesterol efflux. The findings here are preliminary and contradictory, making it hard to translate the evidence on most of these naturally occurring agents into clinical applications.